Pengaruh Media Gambar Terhadap Kemampuan Membaca Permulaan Siswa Kelas 1 Sekolah Dasar - Putri, Putri; Misrina, Misrina; Hayati Siregar, Rahma (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the effect of picture media on the beginning reading ability of first-grade elementary school students. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research population consisted of all first-grade students of SD Negeri 8 Tanah Luas, North Aceh, totaling 46 students, who were selected as the sample through a total sampling technique. Class IB was assigned as the experimental group, while Class IA served as the control group. The research instrument was a beginning reading ability test administered in the form of a pretest and posttest. Data were analyzed using descriptive statistics and an Independent Samples t-test with the assistance of SPSS. The results showed that the mean posttest score of the experimental group was higher than that of the control group (86.74 > 74.61). In addition, the obtained value of tcalculated > ttable​ (4.392 > 1.680) with a significance level of 0.000 < 0.05 indicated a statistically significant difference between the two groups. Therefore, it can be concluded that the use of picture media has a positive and significant effect on the beginning reading ability of first-grade elementary school students.